SWEAR WORD FOUND IN WE HAVE A GHOST MOVIE - Adriati, Rini; Nur, Frina Diniarta; Akbar, Aulul Miftahurizki (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
Abstarct: The purpose of this research is to determine the swear word, the type of swear word, and the motive for swearing that are found in We Have a Ghost movie. The data in this research is obtained from We Have a Ghost movie directed by Christopher B. Landon. In conducting this research, the method used is qualitative method. The theories used in analyzing the swear word are the theory of Horan (2011, in Permadi, 2017), the theories used in analyzing the type of swear word are the theory by Jay (2008), and the theories used in analyzing the motive for swearing are the theories by Karjaleinen (2002, in Permadi, 2017). Based on the analysis, the writers found 58 data of swear words and 4 type of swear words, namely expletive swear words (30 data), abusive swear words (6 data), humorous swear words (9 data), and auxiliary swear words (13 data). The writers also found 3 motives for swearing, namely psychological motive (42 data), social motive (10 data), and linguistic motive (6 data). Keywords: Swear Words, Types, Motives, We Have a Ghost Movie